Pemberdayaan Masyarakat Melalui Pelatihan Ms Excel Pada Staf Kantor Desa Giri Sasak - sulaiman sarmo; I Dewa Gde Bisma; Iwan Kusuma Negara (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
Microsoft Excel is an administrative application that is very easy to operate and is commonly used in all lines of life today. So far, the village office staff has stored important data and documents in the village archives so that when needed it is difficult to find these documents. There for we need a more adequate village archive called a village profile. This village profile will be designed on a computer-based basis using Ms Excel so that it will make it easier for village staff to input data related to the actual state of the village. This service activity aims to increase understanding of Ms Excel, by providing knowledge about the operation of Ms Excel, as well as tools that can be used to design village profilers. The method used is to conduct skills training, including lectures, questions and answers. Demonstration, practice or practice, display. The results of the training show that the village staff are able to operate Ms Excel well. In addition, they are also able to design a simple village profile model and can input population data in the Giri Sasak village